Program of the Department of Transportation in Improving Public Transportation Services: Program Dinas Perhubungan dalam Meningkatkan Pelayanan Angkot - Armianti, Febba; Riyadh UB, Ahmad (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the program of the Department of Transportation in improving public transportation services in Sidoarjo Regency. This research is based on the fact that angkot services in Sidoarjo Regency have not been maximized. Problems with public transportation are still found in Sidoarjo Regency, this can be seen from the fact that there are still many people who choose to use online transportation instead of using public transportation, there are still many people who complain about the badness and comfort of angkot. The research method used in this research is using descriptive qualitative, data collection is done through interviews, observation, and documentation, as well as data analysis techniques used in this study refers to the theory of Miles and Huberman. The results showed that the program carried out by the Transportation Service of Sidoarjo Regency to improve public transportation services in Sidoarjo Regency regarding the achievement of goals could be said to have not been fully successful, as evidenced by the large number of angkot drivers who did not comply with the regulations, but related after the provision of exemplary servant training by members of the Police. However, there are several angkot drivers who have complied with the regulations. The exemplary service training was provided with facilities in the form of uniforms, id cards, trash bins and medicine towns. The strategy to overcome this angkot service is also to carry out active socialization of the health program to angkot drivers and passengers to prevent the corona virus.